PKS IVAStar - An Overview of Chatbot Development (Borneo Engineering & Advanced Multidisciplinary International Journal, 2023)
Over the past decade, the advancements in technologies such as artificial intelligence (AI), big data, and internet of things (IoT) have greatly influenced various industries. Among these applications, chatbots have emerged as a notable example. Chatbots like intelligent virtual assistants (IVAs) are becoming increasingly popular in various fields such as healthcare, education, and customer service. IVAs are software assistants that are able to interact with users to support meaningful tasks, identify information needs, provide relevant information, and improve their performance based on user feedback.  It's like a robot that answers questions or provides information needed by users in the form of conversations or text messages. The use of artificial intelligence in chatbot enables users to quickly and easily obtain relevant information based on the information provided. PKS IVAStar is a computer chatbot programme that uses artificial intelligence and natural language processing. It was created to make it simpler for the Student Affairs Department to provide feedback to users. A research model based on rules-based chatbot that sets information and provides responses based on a set of predefined rules with the use of pattern matching algorithms. The effectiveness of a chatbot depends on several factors, such as the quality of the natural language processing algorithms. It is important to consider the level of human oversight and intervention that is necessary. In future, PKS IVAStar could involve exploring advanced machine learning techniques, such as deep learning and reinforcement learning, to enhance the performance and adaptability of AI chatbots in delivering an improved online customer experience.